Pengaruh variabel-variabel di sektor riil dan perbankan terhadap Shock Credit Default Swap (CDS) di Indonesia - Dwi Hastuti; Muhammad Edhie Purnawan; Sunargo Sunargo (e-Journal Perdagangan Industri dan Moneter, 2019)
The rapid development of the global financial market today is getting faster and integrated with the existence of advanced technology. Along with economic issues in various worlds, directly related to the global economic crisis that occurred in 2008-2009 greatly influenced the development of credit default swaps (CDS) in developing countries such as Indonesia. The increase in the value of the credit default swap, which carries a high risk of default, will further impact investor confidence and weaken the exchange rate. This is reflected in the shocks of the global crisis and the subprime mortgage prime in the United States. However, the onset of a global crisis can be early with early indicators of crisis from credit default swaps so that crisis management can be carried out faster. The results of this study indicate that the credit default swap is responded to faster by the banking sector than the real sector. Keywords: Financial crises, Credit Default Swap (CDS), Riil and banking sector